EFEKTIVITAS CANGKANG TELUR AYAM RAS (Gallus gallus domesticus) SEBAGAI KARBON AKTIF DENGAN AKTIVATOR NaOH - Teguh Nurandi (FT-USNI, 2021)
Industrial activities are one source of waste whose activities produce residues, both in the form of liquid and solid waste, one of the efforts to reduce waste is to reuse waste generated from the production process, one of which is eggshell waste. In this study the authors used egg shells that were used as activated carbon and were applied to wastewater samples with parameters for testing pH, COD and BOD. Activated carbon is made from 3 variations of temperature namely 400 oC, 500 oC and 600 oC. Furthermore, activated carbon was applied to the wastewater sample. From the test results obtained the most optimum combustion temperature is at a temperature of 600 oC. The pH at the combustion temperature of 600 oC increased from 4,627 (acid) to 7,313 (neutral) and decreased the BOD level down from 454,333 mg / L to 173,667 mg / L, and the COD content decreased from 1517,667 to 598,667.